Addressing the transition to sustainable energy systems: Special issue dedicated to the 2018 conferences on Sustainable Development of Energy, Water and Environment Systems (SDEWES). (March 2020) - Pukšec, Tomislav; Markovska, Natasa; Foley, Aoife; Duić, Neven
Abstract: This editorial in Renewable and Sustainable Energy Reviews (RSER) is a virtual special issue (VSI) dedicated to the three conferences on Sustainable Development of Energy, Water and Environment Systems (SDEWES) held in 2018. These included the 13th SDEWES Conference (30 September to the 4 October in Palermo, Italy), the 3rd South East European SDEWES Conference (30 June to 4 July in Novi Sad, Serbia and the 1st Latin American SDEWES Conference (28–31 January in Rio de Janeiro, Brazil). In line with the RSER's policy, this VSI published two types of articles, either high quality review papers or original research papers with a strong review component. The guest editors invited 55 extended articles presented at the 2018 SDEWES conferences. These articles went through rigorous peer review process, and a total of 17 articles were finally accepted and published in this VSI. This editorial overviews these articles and examines their contribution to the field. In addition this editorial also provides an overview of the SDEWES 2018 conference series in order to reflect the continuous research efforts of the SDEWES research community and knowledge body on topics such as sustainable mobility, energy storage systems, various sustainability assessments, renewable energy source (RES) potential and biorefineries.